Evolutionary psychology : a beginner's guide : human behaviour, evolution, and the mind - Dunbar, Robin; Barrett, Louise; Lycett, John. (Oxford : Oneworld, 2006)
Offering straightforward explanations of everything from the 'gene's eye view' to the 'nature versus nurture' debate, this accessible guide also tackles the major controversies while assessing the potential of evolutionary psychology to make profound differences to the way we think about human nature.
Includes bibliographical references and index.
Keywords: Biological Evolution; Evolutionary psychology; Cultural Evolution